(untitled) (Revista de Ciências Agroveterinárias, 2016)
Boldo (Peumus boldus Molina) is a tree of the Monimiaceae family. It is used by the people to treat several diseases, and presents diverse products such as: a bactericide, an insecticide and an allelopathy. The aim of this study was to evaluate the potential of the allelopatic activity of the boldo infusion on the germination and initial development of lettuce and cucumber seeds. The bioassay was conducted in an environmental temperature controlled laboratory, through a completely randomized design method with five repetitions. The boldo infusion was obtained in the local commerce, and prepared with boiling distillated water, diluted to the proportions of 25, 50, 75, and 100%. The control was only distillated water. The evaluation parameters used were germination percentage, germination speed index (measured each 24 hours) and root length (measured with a caliper rule on the last day of the experiment). Regarding germination percentage, we found significant values only using 100% treatment of cucumber seeds. The germination of lettuce seeds was inhibited throughout all of the treatments with boldo infusion. The germination speed index of cucumber seeds was influenced throughout all of the treatments. The root length of cucumber seeds was inhibited with all treatments and significantly different if compared with the control. Boldo infusion presented allelopathic activity on the seeds of lettuce and cucumber, showing the presence of bioactive molecules which can serve to subsidize new studies.